Cell Communications among Microorganisms, Plants, and Animals: Origin, Evolution, and Interplays - Yves Combarnous; Thi Mong Diep Nguyen (My University, 2020)
Cell Communications among Microorganisms, Plants, and Animals: Origin, Evolution, and Interplays
Keywords: Giao tiếp tế bào; Vi sinh vật/Thực vật/Động vật; Tiến hóa